VALUES OF CHARACTER EDUCATION IN DRAMA BUNGA SEMERAH DARAH AND ITS IMPLICATIONS IN LEARNING LANGUAGE IN SMA - Feralisa Usmarianti; Munaris Munaris; Iqbal Hilal (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2022)
The focus of this research will be on how the values of character education in the drama Bunga Semerah Darah by W.S Rendra and their implications in learning Indonesian in high school are discussed. The method in this research is a qualitative descriptive method. The source of research data is the drama Bunga Semerah Darah by W.S Rendra. The research data is the dialogue between the characters in the drama which contains the values of character education. The results of this study indicate that the values of character education in the drama Bunga Semerah Darah are religious values, honest values, tolerance values, discipline values, hard work values, independent values, democratic values, creative values, curiosity values, values appreciating achievements, friendly or communicative values, peace-loving values, social care values, and responsibility values. Fokus penelitian ini akan membahas bagaimana nilai-nilai pendidikan karakter dalam drama Bunga Semerah Darah karya W.S Rendra dan implikasinya dalam pembelajaran bahasa Indonesia di SMA.  Metode dalam penelitian ialah metode deskriptif kualitatif.  Sumber data penelitian ialah drama Bunga Semerah Darah karya W.S Rendra. Data penelitian adalah dialog antar tokoh dalam drama tersebut yang mengandung nilai-nilai pendidikan karakter. Hasil penelitian ini menunjukkan bahwa nilai-nilai pendidikan karakter dalam drama Bunga Semerah Darah adalah nilai religius, nilai jujur, nilai toleransi, nilai disiplin, nilai kerja keras, nilai mandiri, nilai demokrasi, nilai kreatif, nilai rasa ingin tahu, nilai menghargai prestasi, nilai bersahabat atau komunikatif, nilai cinta damai, nilai peduli sosial, dan nilai tanggung jawab. Keyword: the value of character education, drama, and learning Indonesian.